Massive and Spontaneous Recurrent Hemorrhage in a Neurofibromatosis Patient with Severe Pectus Carinatum and Huge Mediastinal Neurofibroma (Annals of Medical Research, 2021)
None
Keywords: Neurofibromatosis; Massive Hemorrhage; Spontaneous; Mediastinum.